2021
DOI: 10.3389/fmicb.2021.662686
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis and Immune Evasive Mechanisms of Equine Herpesvirus Type 1

Abstract: Equine herpesvirus type 1 (EHV-1) is an alphaherpesvirus related to pseudorabies virus (PRV) and varicella-zoster virus (VZV). This virus is one of the major pathogens affecting horses worldwide. EHV-1 is responsible for respiratory disorders, abortion, neonatal foal death and equine herpes myeloencephalopathy (EHM). Over the last decade, EHV-1 has received growing attention due to the frequent outbreaks of abortions and/or EHM causing serious economical losses to the horse industry worldwide. To date, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 104 publications
(126 reference statements)
0
23
0
Order By: Relevance
“…2 Zhaosu Horse Barn in Yili, Zhaosu, China. 3 Center of Animal Disease Control and Prevention, Acheng District, Harbin, Heilongjiang, China. 4 Cisen Pharmaceutical Co., Ltd, Jining, Shandong, China.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Zhaosu Horse Barn in Yili, Zhaosu, China. 3 Center of Animal Disease Control and Prevention, Acheng District, Harbin, Heilongjiang, China. 4 Cisen Pharmaceutical Co., Ltd, Jining, Shandong, China.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Equid herpesvirus 1 (EHV-1), classified within the family Herpesviridae, the subfamily Alphaherpesvirinae and the genus Varicellovirus [1], is one of the most serious viral pathogens of the horse population as it is frequently associated with abortion, respiratory problems as well as both ocular and neurological diseases in horses. As such, it can have a significant impact not only on equine health but also on the overall equine industry around the world [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Then, EHV-1 infects lymphocytes and subsequently reaches the blood circulation [ 3 , 4 ]. The cell-associated viraemia induces a dissemination of the virus to secondary sites of infection, such as the central nervous system (CNS), the uterus or the eye [ 5 ]. Several studies have suggested that EHM is associated with a single-nucleotide polymorphism at position 2254 in the EHV-1 DNA polymerase gene (ORF 30) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…EHV-1 is one of the major infectious agents affecting horses worldwide. The virus is responsible for respiratory disorders, abortion, neonatal foal death, and equine herpes myeloencephalopathy [16]. The main portal of EHV-1 entry is the upper respiratory tract.…”
Section: Introductionmentioning
confidence: 99%